Shared decision-making and parental experiences with health services to meet their child's special health care needs: Racial and ethnic disparities. Issue 10 (October 2018) - Jolles, Mónica Pérez; Lee, Pey-Jiuan; Javier, Joyce R.
Highlights: Families engaged in SDM had lower odds of reporting service dissatisfaction. Fewer minority parents reported SDM engagement compared to whites. Blacks engaged in SDM were more likely to report negative service experiences. This disparity was no longer significant after adjusting for covariates. Abstract: Objectives: Test the relationship between shared decision-making (SDM) and parental report of frustration with efforts to get services for their child and to address unmet health needs; assess SDM's influence on minority parents' service experiences. Methods: Performed secondary analysis using the 2009–2010 National Survey of Children with Special Health Care Needs (n = 40, 242). Used multivariate logistic regressions to test the association between SDM and parent-reported service experiences, and whether SDM influenced the association between minorities and negative service experiences. Propensity scores accounted for observed selection bias. Results: Families engaged in SDM had lower odds of reporting service dissatisfaction. Fewer minority parents reported SDM engagement compared with Whites (between 62% and 66% versus 74%). Blacks engaged in SDM had higher odds of reporting negative service experiences compared with SDM-engaged Whites. This disparity was no longer significant after adjusting for covariates. Conclusion: SDM is associated with lower reports of parental service dissatisfaction. Stratified analyses showed that SDM seems to be experienced differently across minority groups. Practice implications: SDM may be a promising engagement strategy to improve parental service experiences. The role of SDM on increasing Black parents' reports of service dissatisfaction, perhaps due to increased awareness of service challenges, should be investigated.